analysis of polymetric -strip reinforced-soil walls adjacent to the rock foundations - M. S. Ramezani; A. Komakpanah (مهندسی عمران شریف, 2024)
In some roadway projects, especially in a mountainous region, the mechanically stabilized earth walls must be constructed in front of stable features such as a rockface for a variety of reasons, including the construction of new roadways, widening of urban transportation corridors, and reduction of rockfall risk. There has been limited research into the dynamic performance of the MSE wall adjacent to the rock slope; thus, the seismic behavior of this retaining system is still poorly understood. The most common methods for seismic stability analyses of reinforced-soil retaining walls are based on pseudo-static limit-equilibrium approaches, where seismic coefficients are applied to the potential failure soil mass. In the pseudo-static method, the assignment of an appropriate lateral seismic coefficient (Kh) that would be able to simulate the seismic inertial force induced in the sliding wedge has a considerable effect on the accuracy of the analyses. Since earthquake acceleration is the main cause of the inertial force induced in the failure mass, the seismic acceleration coefficient (Kh) is determined mostly based on the peak ground acceleration at the wall base level. The seismic events are transient in nature, and the earthquake-induced forces vary in intensity during vibrations. However, in the pseudo-static method, the seismic force is applied to the failure soil mass indefinitely. Therefore, the use of peak ground acceleration could lead to over-conservative results. To overcome this limitation, the seismic coefficient is usually expressed as a fraction of the peak ground acceleration for design purposes. The value of this fraction has not been clearly defined for reinforced-earth retaining walls. Most of the proposed methods for calculating the seismic acceleration coefficient are based on theoretical assumptions, and the validation of this important parameter has not been evaluated based on an experimental approach. In this study, initially, the seismic behavior of the polymeric-strip reinforced-earth retaining walls built on the rock foundation is investigated using shaking table tests. Then, the assumptions of the pseudo-static approach are simulated by push-back pressure tests. To apply back pressure to a model wall, a special apparatus was designed and made in the Tarbiat Modares University laboratory. Finally, the horizontal seismic coefficient is estimated by comparing and adjusting the result of the shaking table and push-back pressure tests. The results presented are based on the acceptable seismic performance of the retaining wall and are compared with the previously proposed relations and AASHTO design code.